The Effects of Time Management and Learning Motivation on Academic Procrastination among Office Management Students at SMKN 51 Jakarta - Chelsea Rizka; Darma Rika Swaramarinda; Dewi Nurmalasari (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Pahlawan Tuanku Tambusai, 2026)
This study aimed to examine the effects of time management and learning motivation on academic procrastination among students enrolled in the Office Management and Business Services Program at SMKN 51 Jakarta. A quantitative approach employing an explanatory research design was adopted. The sample consisted of 141 students selected through proportional random sampling. Data were collected using a validated and reliable five-point Likert questionnaire and analyzed through multiple linear regression using IBM SPSS Statistics 27. The findings revealed that time management had a significant negative effect on academic procrastination (β = -0.610, t = -14.524, p < .001). Likewise, learning motivation also exerted a significant negative influence on academic procrastination (β = -0.445, t = -11.250, p < .001). Simultaneously, both variables significantly predicted academic procrastination (F = 157.527, p < .001) and explained 69.5% of its variance (R² = .695). These findings indicate that students with stronger time management skills and higher learning motivation tend to demonstrate lower levels of academic procrastination. The study concludes that strengthening students' time management competencies and learning motivation is essential for reducing procrastination behavior and improving academic performance in vocational education.